REFINEMENTS OF -DUALITY THEOREMS FOR A NONCONVEX PROBLEM WITH AN INFINITE NUMBER OF CONSTRAINTS - Son, T. Q. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
Some remarks on approximate optimality conditions of a nonconvex optimization problem which has an infinite number of constraints are given. Results on ε-duality theorems of the problem are refined by using a mixed type dual problem of Wolfe and Mond-Weir type.